2007
DOI: 10.1074/jbc.m705194200
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dual Effects of Parathyroid Hormone on Skeletal Gene Expression in Vivo by Microarray and Network Analysis

Abstract: Parathyroid hormone (PTH) stimulates bone formation when injected daily but causes severe bone loss with continuous infusion. The mechanism of its paradoxical effects is still elusive. In this study, we compared changes in the gene expression profile in bone induced by intermittent or continuous treatment with three different PTH peptides, PTH-(1-34), -(1-31), and -(3-34), in Sprague-Dawley female rats. PTH-(1-34) regulated numerous genes (ϳ1,000), but differentially, in both regimes. PTH-(1-31) regulated a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
148
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(158 citation statements)
references
References 41 publications
9
148
1
Order By: Relevance
“…It also may inhibit apoptosis in mature osteoblasts, which might prolong the anabolic effects of PTH. (12)(13)(14)(15)(16)(17)(18)(19)30) However, to fully appreciate the responses of bone to PTH, it is also necessary to understand how PTH administration affects other type of cells in the bone microenvironment that are implicated in bone turnover. Osteoclasts are another potential target of PTH action because the physiologic activities of osteoblasts and osteoclasts are tightly coupled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also may inhibit apoptosis in mature osteoblasts, which might prolong the anabolic effects of PTH. (12)(13)(14)(15)(16)(17)(18)(19)30) However, to fully appreciate the responses of bone to PTH, it is also necessary to understand how PTH administration affects other type of cells in the bone microenvironment that are implicated in bone turnover. Osteoclasts are another potential target of PTH action because the physiologic activities of osteoblasts and osteoclasts are tightly coupled.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous administration of PTH induces catabolic effects on bone, whereas intermittent PTH administration exerts anabolic effects. (12)(13)(14)(15)(16)(17)(18)(19) Currently, once-daily injection of human PTH is approved by the Food and Drug Administration as treatment for osteoporosis in the United States. In addition, it could have potential for the treatment of other conditions that require new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of specific PPRexpressing T-cell subpopulations, 6,7 PTH actions on hematopoiesis are thought to be mediated via paracrine or juxtacrine signaling from PPR-activated stromal osteoblastic cells. 1,2,8 PPR signaling in stromal osteoblastic cells alters the expression of osteoclastic cytokines, most notably receptor activator of nuclear factor-B ligand (RANKL) and osteoprotegerin (OPG), which regulate the differentiation of hematopoietic cells to mature bone resorbing osteoclastic cells. 8 -12 More recent studies have focused on the role of PTH actions on HPCs.…”
mentioning
confidence: 99%
“…A number of microarray studies of PTH-treated whole bone or osteoblasts have identified thousands of genes regulated by PTH. (21)(22)(23) Many of these genes have been identified to play a role in PTH anabolic action in studies of knockout mice, including transcription factors ATF4 (18) and CREM (24) ; signaling molecules such as b-arrestin (25) ; cytokines such as fibroblast growth factor 2 (FGF2), (16) interleukin 18 (IL-18), (15) and insulin-like growth factor 1 (IGF-1) (26) ; matrix proteins including osteonectin (27) ; and other factors that regulate Wnt pathway signaling including secreted Frizzled-related protein 1 (sFRP-1). (28,29) Surprisingly, given the results in SOST transgenic mice, anabolic treatment with PTH was just as effective in the absence of low density lipoprotein receptorrelated protein 5 (LRP5) as in wild-type mice.…”
mentioning
confidence: 99%